PENGARUH MOTIVASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PADA KANTOR DESA KECAMATAN BESUKI KAB SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Khomariyah, Siti Nur; Wahyuni, Ika; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2025)
Human Resource Management (HRM) is a systematic process carried out by an organization to manage human resources—such as recruiting, training, developing, motivating, and retaining employees—to achieve organizational goals. A proper systematic process is thus essential in analyzing the influence of motivation, work discipline, and work environment on performance at the village offices in the Besuki Sub-district, Situbondo Regency, with job satisfaction as an intervening variable. The population in this study consists of village officials from Kalimas, Blimbing, and Langkap. The sampling method was determined using probability sampling. Data analysis and hypothesis testing were conducted using Structural Equation Modeling – Partial Least Squares (PLS-SEM).The results of the direct influence hypothesis test using SmartPLS 3.0 show that motivation has a significant effect on Job Satisfaction, Work Discipline has a significant effect on Job Satisfaction, and the Work Environment has a significantly positive effect on Job Satisfaction. Motivation, Work Discipline, and Work Environment each significantly affect performance, and Job Satisfaction significantly affects performance. The indirect influence hypothesis test results indicate that Motivation, Work Discipline, and Work Environment each have a significant effect on Performance through Job Satisfaction as a mediating variable.